ANALISIS PERILAKU BULLYING MENURUT PANDANGAN TEORI KEPRIBADIAN SERTA IMPLIKASINYA BAGI BIMBINGAN DAN KONSELING - Wiantina, Nur Azmi (JIEGC Journal of Islamic Education Guidance and Counselling, 2021)
Most definitions of bullying are categorized as a part of aggressive behavior involving the intention to hurt other people. Bullies have high score on psychoticism, physical strength, attitude towards violence, extroversion. Self-esteem bullies are higher than victims in all of these dimensions. Bullies have aggressive, impulsive behavior, not feeling guilty, and do not feel empathy towards the victims, if seen from Eysenck’s personality dimension, this is a part of extravert neurotic. Intervention strategies to handle bullying at school, and creating more peaceful school environment could be seen as an important moral action. More researches about the effective programs to handle bullying are needed; also the longitudinal effect for bullies and victims of physical bullying, verbal bullying, and cyber bullying also need to be researched